A strategy to improve exclusive breastfeeding through prenatal and postnatal information and communication, Cali (Colombia): 2014-2017 - Restrepo-Nieto, Natalia; Herrera-Medina, Rodolfo; Fuertes-Bucheli, José F.; Osorio-Murillo, Olga; Castro-Valencia, Claudia (Universidad y Salud, 2023)
Introduction: Accomplishing exclusive breastfeeding goals has been a challenge. Objective: To assess the effectiveness of a strategy to promote and achieve exclusive breastfeeding during the first months of life. Materials and methods: A quasi-experimental randomized non-masked study was carried out during the 2014-2017 period. Adult first-time pregnant women at gestational age between 12-27 weeks from Cali, Colombia were included. While the control group received standard care only, the intervention group was also subjected to a prenatal and postnatal strategy that included information and communication technologies. Follow-up was carried out until 6 months postpartum. Results: The 141 participants were distributed in two groups: control (73) and intervention (68). The mean adherence to exclusive breastfeeding was greater in the intervention group (1.1 ± 0.65, p<0.001), reaching an average of 4.8 months (IC95%=[4.4; 5.3]). The control group was 11.68 times more likely to end exclusive breastfeeding during the first six months postpartum as compared to the intervention group. Conclusion: The incorporation of prenatal and postnatal counseling through information and communication technologies promoted a sustained exclusive breastfeeding.